2016
DOI: 10.1590/s0100-204x2016000900071
|View full text |Cite
|
Sign up to set email alerts
|

Variabilidade espacial de atributos físicos de solo coeso sob sistemas de manejo convencional e de plantio direto

Abstract: Resumo -O objetivo deste trabalho foi avaliar a variabilidade espacial da umidade, da densidade e da porosidade de solo coeso cultivado com soja sob sistemas de manejo convencional e de plantio direto. Foram instaladas duas malhas regulares, uma para cada tipo de manejo. O solo foi coletado na profundidade de 0,00-0,20 m, e a variabilidade espacial de seus atributos foi analisada por meio de parâmetros do semivariograma e do interpolador geoestatístico krigagem ordinária. O solo apresentou maior densidade e co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
12
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 10 publications
(8 reference statements)
3
12
0
2
Order By: Relevance
“…The coefficient of variation (Table 2) revealed low variability for soil bulk density (BD) at all depths and total porosity (TP) at a 0.0 -0.1 m depth, similar to the results of Ribeiro et al (2016), who observed the spatial variability of cohesive soil physical attributes submitted to conventional management and direct seeding methods. Penetration resistance (PR) for 0.1 -0.2 m and 0.2 -0.3 m depth, gravimetric moisture (GM) for all depths, TP for 0.1 -0.2 m and 0.2 -0.3 m depth, and hydraulic conductivity (K 0 ) all had moderate variability.…”
Section: Resultssupporting
confidence: 82%
“…The coefficient of variation (Table 2) revealed low variability for soil bulk density (BD) at all depths and total porosity (TP) at a 0.0 -0.1 m depth, similar to the results of Ribeiro et al (2016), who observed the spatial variability of cohesive soil physical attributes submitted to conventional management and direct seeding methods. Penetration resistance (PR) for 0.1 -0.2 m and 0.2 -0.3 m depth, gravimetric moisture (GM) for all depths, TP for 0.1 -0.2 m and 0.2 -0.3 m depth, and hydraulic conductivity (K 0 ) all had moderate variability.…”
Section: Resultssupporting
confidence: 82%
“…For these authors, physical properties of the soil that show strong spatial dependency are most influenced by the soil forming factors (intrinsic properties), whereas moderate spatial dependence will probably be the result of agricultural practices such as soil amendment, fertilization, liming, and machinery traffic, among others (extrinsic properties). Similar classification were found by Aquino et al (2014) for clay and total sand fractions and BD; by Ribeiro et al (2016) for BD and TP; by Leão et al (2010) for clay and silt fractions; and by Silva and Lima (2013a) for clay and BD. Lima et al (2006; confirmed that the lower the SDI (the proportion between the nugget effect in relation to the sill), the higher the spatial dependence of the soil physical properties under study will be.…”
Section: Results and Discusionsupporting
confidence: 79%
“…Of those papers, 107 reported SWC semivariograms, 19 compared SWC semivariograms within or among long-term land uses or ecosystem types (e.g., agricultural vs. grassland, forest vs. pasture), and only 2 compared SWC semivariograms among soil or residue management practices in crop production fields (Table 1). These two publications are Panosso et al (2009) and Ribeiro et al (2016), who evaluated long-term sugarcane (Saccharum L.) residue management and long-term tillage/cover-crop management of soybean [Glycine max (L.) Merr. ], respectively, in Brazil.…”
mentioning
confidence: 99%